Crashworthiness of foam-filled and reinforced honeycomb crash absorbers in transverse direction - Nicoud, Guillemin; Ghasemnejad, Hessam; Srimanosaowapak, Sompong; Watson, James W. (Springer, 2024)
Honeycomb crash absorbers have been widely studied as energy absorption devices for use in automotive industries. However, none of these investigations have studied the side impact of empty and foam-filled honeycomb absorbers and adding stiffeners between the different layers of the corrugated sheets which are composing the honeycomb structure to analyse the structure under transverse (L-direction) impacts. In this paper, the foam-filled and reinforced honeycomb crash absorbers are investigated under axial (T) and transverse (L) loading directions. Experimental results for both empty and foam-filled specimens under quasi-static and impact loads were implemented to validate the developed finite element model. Finite element analysis (FEA) was performed to find out the crashworthiness behaviour of the structure under axial and transverse impacts according to road conditions. Finally, a new design of stiffened honeycomb crash absorber was developed and investigated to reduce the level of acceleration experienced by the passengers during the crash event. In this regard, it is concluded that all the requirements related to the energy absorption capabilities and generated deceleration under impact loading can be met by introducing an advanced method to reinforce honeycomb absorbers using stiffeners. It is also proven that the thickness of these stiffeners will not significantly influence the force levels. Due to increase of wall thickness from 1 to 3 mm, the mean crushing force increased from 129 kN to 148 kN. This growth is not sufficient as the goal is to obtain a mean crushing force of 300 kN. Thickening the stiffeners would lead to a loss of efficiency of the structure, as the small increase in mean force would not make up for the gain in mass. Thus, increasing the corrugated sheet’ thickness becomes necessary.
Keywords: Aluminium honeycomb; Aluminium foam; Foam-filled structures; Stiffeners